KEWENANGAN PEMERINTAH DAERAH DALAM PENGEMBANGAN PENDIDIKAN DI MA’HAD AL-ZAYTUN MENURUT PERATURAN DAERAH KABUPATEN INDRAMAYU NO. 8 TAHUN 2015 - Abdur Rahim; Vina Alfiyah; Firly Alvia Yasmin; Naufal Jazilunnawal; Ikmal Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Indonesia as a legal state emphasizes that education is an element of national development. Indramayu Regency Regional Regulation Number 8 of 2015 concerning Education in Indramayu Regency stipulates in Article 14 Paragraph 1 that the regional government has the authority to assign education services and related parties to organize spiritual education. This research uses qualitative research using secondary data sources. The foundation of Al-Zaytun Islamic boarding school can instill the values ​​of independence, togetherness and love of knowledge which are based on akhlaq al-karimah and devotion to God. In Regional Regulation No. 8 of 2015, several articles and verses are mentioned that refer to discussions on developing educational levels. In this research, Ma'had Al-Zaytun develops education gradually and periodically, starting from Madrasah Aliyah and Tsanawiyah, continuing to Madrasah Ibtidaiyah, continuing to the Institute of Religion. Islam Al-Zaytun Indonesia (IAI Al-Azis), and finally PAUD. The authority of the Regional government is contained in Regional Regulation no. 8 of 2015, Indramyu Regency in terms of education provides convenience in undergoing educational development in Ma'had Al-Zaytun. With the existence of Regional Regulation no. 8 of 2015 is also a big step for education in Ma'had Al-Zaytun in following Government regulations and not going off the established path. Keywords: Authority, Government, Educational development;